Ramf: An Open-Source R Package for Statistical Analysis and Display of Quantitative Root Colonization by Arbuscular Mycorrhiza Fungi - Chiapello, Marco; Das, Debatosh; Gutjahr, Caroline (Frontiers in Plant Science, 2019)
Data analysis and graphical representation form an essential part of scientific research dissemination. The life-science community is moving towards a more transparent presentation of single data points or data distributions and away from mean-values displayed as bar charts. To facilitate transparent data display to the mycorrhiza community, we present “Ramf” an open-source R package for statistical analysis and preparation of a variety of publication-ready plots, custom-made for analyzing and displaying quantitative root colonization by arbuscular mycorrhiza fungi or any kind of data to be displayed in the same format. Ramf replaces the scripting needed for data analysis and can be readily used by researchers not acquainted with R. In addition, the package is open to improvements by the community. Ramf is available at https://github.com/mchiapello/Ramf.